Use of silicones in fixed aesthetic rehabilitations: clinical case - Taumaturgo, Vandre Mesquita; Leal, Lícia Camila Rocha; Vasques, Evamiris França Landim; Silva, Maria Daniela Balbino; Lima, Edson Vaz; Landim, Taciana França (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Molding in a fixed prosthesis is one of the most important stages in rehabilitative treatment, as it is there that attempts are made to reproduce dental preparations and adjoining regions by using appropriate materials and techniques. Among the fixed prosthesis molding materials available on the market, the elastomers stand out, which are polymers where the prey occurs through the increase of the chain and the establishment of cross-links. The objective of the study is to present a clinical case and perform a literature review on the use of condensation silicone and addition to molds in Fixed Prosthesis. In this literature review, a survey of PubMed, Scielo and Lilacs data was performed, using the descriptors: Denture, Partial, Fixed; Dental Impression Materials and Elastomers. It is possible to conclude that in the field of Dentistry, the elastomers, among them the condensation-cured and addition-cured silicones, both provide high precision models and are the most used materials in works with fixed partial dentures. Therefore, it is up to the professional to know the properties and adapt to the best group of chosen materials.